Book review: Silniki stacjonarne na ziemiach polskich [Stationary Engines on Polish Lands] - Zaradzki, Bartosz (Studia Historiae Oeconomicae, 2024)
The book Silniki stacjonarne na ziemiach polskich [Stationary Engines on Polish Lands] was written by Grzegorz Smela, Marek Wiśniewski and Andrzej Zwierniak and published in 2022 by the Ruthenus. Grzegorz Smela and Andrzej Zwierniak are passionate about old agricultural technology are also both co-authors of the book Polskie silniki stacjonarne i ich producenci w XIX i XX wieku [Polish Stationary Engines and their Manufacturers in the 19th and 20th Centuries; Smela and Zwierniak, 2020]. In addition, Grzegorz Smela is one of the initiators of the creation of the Museum of Stationary Engines and Agricultural Technology in Konieczkowa (Poland). This time the authors invited Marek Wiśniewski, M.Sc., who is a curator and head of the agricultural technology department at the Rev. Krzysztof Kluk Museum of Agriculture in Ciechanowiec (Poland).